2013
DOI: 10.1007/s00415-013-6979-y
|View full text |Cite
|
Sign up to set email alerts
|

Teriflunomide reduces relapse-related neurological sequelae, hospitalizations and steroid use

Abstract: Multiple sclerosis (MS) relapses impose a substantial clinical and economic burden. Teriflunomide is a new oral disease-modifying therapy approved for the treatment of relapsing MS. We evaluated the effects of teriflunomide treatment on relapse-related neurological sequelae and healthcare resource use in a post hoc analysis of the Phase III TEMSO study. Confirmed relapses associated with neurological sequelae [defined by an increase in Expanded Disability Status Scale/Functional System (sequelae-EDSS/FS) ≥30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 15 publications
6
39
0
Order By: Relevance
“…These results are consistent with those observed in a similar analysis of the Phase III TEMSO study [13]. Thus, in conclusion, teriflunomide has demonstrated consistent and beneficial outcomes on relapses with sequelae and relapses requiring healthcare resources compared with placebo across two Phase III clinical trials.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are consistent with those observed in a similar analysis of the Phase III TEMSO study [13]. Thus, in conclusion, teriflunomide has demonstrated consistent and beneficial outcomes on relapses with sequelae and relapses requiring healthcare resources compared with placebo across two Phase III clinical trials.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with those seen in the TEMSO study [13] and supplement the limited number of studies associating disease-modifying therapies with fewer hospitalizations [1619]. Limiting the number of nights spent in hospital is a challenge.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…3,4 Resting and slowly dividing cells are less affected, because the DHODH-independent salvage pathway provides enough pyrimidine. [8][9][10][11][12][13][14][15] In another phase 3 trial (TENERE), the efficacy of 14 mg teriflunomide was similar to high-dose subcutaneous interferon-beta-1a, but treatment satisfaction was greater. [5][6][7] The efficacy and safety of teriflunomide were examined in several clinical trials and follow-up studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the two phase 3 trials of TEMSO and TOWER, 14 mg teriflunomide daily reduced the annualized relapse rate by 31.5% and 36.3%, compared to placebo. [8][9][10][11][12][13][14][15] In another phase 3 trial (TENERE), the efficacy of 14 mg teriflunomide was similar to high-dose subcutaneous interferon-beta-1a, but treatment satisfaction was greater. 16 A fourth phase 3 trial showed reduced risk of relapses defining clinically definite multiple sclerosis (TOPIC).…”
Section: Introductionmentioning
confidence: 99%